What is the solution to the equation below?log7+log(x-4)=1
Ox---
38
O x--18
OX=
OX=
18
3998

Answers

Answer 1
Answer:

Answer:

So, the solution to the equation

log(7)+log(x−4)=log(7)+log(x−4)=1 is x=38/7

, which is approximately 5.43 when rounded to two decimal places.

None of the options provided (38, -18, 18, 3998) match this solution.

Step-by-step explanation:


Related Questions

Consider the function f(x) =x² - 49-x?For which intervals is f(x) positive? Check all that apply.(-0, -3)(-3,-2)O(-2,2)(2,3)(-0,3)
Can anyone help its due in 10 minuets!
2, 10, 50, 250, ...Write a recursive formula for
A bird with a mass of 1.5 kg flies at a rate of 4.0 m/s. What is the kinetic energy of the bird?
Round to the nearest hundredth 5.6192

The Eagles basketball team scored 12 more than 2 times as many points in the last game of the season than in the first game. Which expressions can be used to find the number of points the Eagles scored in the last game? Select all the expressions that apply.

Answers

Answer:

A. 12+2p

G. p+p+12

Step-by-step explanation:

The Eagles basketball team scored 12 more than 2 times as many points in the last game of the season than in the first game

Number of points scored in the last game of the season = 2p + 12

A. 12+2p

Equivalent

B. 2+p+12

= P + 14

Not equivalent

C. 2+12p

Not equivalent

D. p(2+12)

= 2p + 12p

Not equivalent

E. p+2+12

= P + 14

Not equivalent

F. 12p+2p

Not equivalent

G. p+p+12

= 2p + 12

Equivalent

You toss a coin and roll a number cube. Find P(tail and a six).

Answers

there are 6 heads and 6 tails as and outcome so
H-T, H-T, H-T, H-T, H-T, H,T

Heads - 1
Heads - 2
Heads - 3
Heads - 4
Heads - 5
Heads - 6
Tails - 1
Tails - 2
Tails - 3
Tails - 4
Tails - 5
Tails - 6
We have to find the probability of tail and 6 so there is only one tail and a  6
P(tail and a six) = 1/12 = 0.08
hope it helps



There will be 12 possible outcomes. So, the probability of (tail and a sic) would be equal to = 1/12

1/12 is your answer..........

Write 9/12 as a decimal

Answers

9 / 12      3 into 9 is 3 and 3 into 12 is 4

= 3 / 4

= 0.75

2/√3-1 where p and q are integers. Show your working clearly. (b) Express in the form p + √q​

Answers

Answer:

Hi,

1+√(3)

Step-by-step explanation:

(2)/(√(3) -1) \n=(2*(√(3) +1))/((√(3) -1)(√(3) +1))\n=(2*(√(3) +1))/(3 -1)\n\n=\boxed{1+√(3) }

Solve each system using substitution x=-2y=1 x=y-5

Answers

You solve either one for y,but I chose the second one.
Add 5 to both sides and you get
X+5=y
Plug this in to the first equation
X=-2(x+5)+1
I am assuming that is plus one instead of equal since the keys are near each other on a phone.
Back to the math: use the distributive property to get
X=-2x-10+1 now combine terms
X=-2x-9
Add 2x to both sides to get
3x=9
Divide both sides by 3 to get
X=3
Now plug 3 in as x in any of the above
I will choose the second one again
So 3=y-5 subtract 5 from both sides to get
Y=8
So the solution is (3,8)

Rewrite 2x  {}^(2)  + 2y {}^(2)  - 8x + 10y + 2 = 0
in standard form find the center and radius of the circle.show all of your work for full credit​

Answers

Final answer:

The given equation can be rewritten into the form of an equation for a circle with center (h,k) and radius r. After completing the squares for x and y coefficients, we determine the center as (2, -5/2) and radius as 1.

Explanation:

The provided equation is 2x2 + 2y2 - 8x + 10y + 2 = 0.Let's rewrite it in the form of an equation for a circle, which is (x-h)^2 + (y-k)^2 = r^2, where (h,k) represents the center of the circle and r represents the radius:

First, we group the terms related to x and y separately like this: 2(x2- 4x) + 2(y2 + 5y) +2 = 0.

Now, re-arrange the terms to complete the square: 2[(x-2)^2 - 4] + 2[(y+5/2)^2 - (5/2)^2] + 2 = 0.

Re-arrange again, this time to make it equate to zero: (x-2)^2 + (y+5/2)^2 = 1. Hence, the circle's center (h,k) is at (2, -5/2) and the radius (r) is the square root of 1, which is 1.

Learn more about Circle in Standard Form here:

brainly.com/question/29000730

#SPJ2

Answer:

first group x's with x's and y's with y's

then complete the squra with x's and y's

2x^2-8x+2y^2+10y+2=0

2(x^2-4x)+2(y^2+5y)+2=0

take 1/2 of linear coeficient and square

-4/2=-2, (-2)^2=4

5/2=2.5, 2.5^2=6.25

add that and negative inside

2(x^2-4x+4-4)+2(y^2+5y+6.25-6.25)+2=0

factor perfect squares

2((x-2)^2-4)+2((y+2.5)^2-6.25)+2=0

distribute

2(x-2)^2-8+2(y+2.5)^2-12.5+2=0

2(x-2)^2+2(y+2.5)^2-18.5=0

add 18.5 both sides

2(x-2)^2+2(y+2.5)^2=18.5

divide both sides by 2

(x-2)^2+(y+2.5)^2=9.25

that is a circle center (2,-2.5) with radius √9.25